Embodied, relational practices of human and non-human in a material, social, and cultural nexus of organizations - Küpers, Wendelin M.; Justus Liebig University Giessen (My University, 2016)
This article explores the significance of materiality and non- or other-human, espe-cially the role of body and embodiment in relation to intra- and inter-practices in or-ganizations and their culture from a phenomenological perspective and cross-disciplinary approach. Following a Merleau-Pontyian approach, the non-human is discussed in relation to cultural practices in organizational life-worlds. Based on a critique of physicalist empiricism and idealistic rationalism, impasses and limita-tions of naturalist and constructionist approaches towards culture are problematized. Showing the co-constitutive role of the in(ter)-between and inter-corporeality allows interpreting the corporeal nexus of material, social, and cultural phenomena of inter-practices within a continuum of the human and non-human, thus as an entangled non-+-human web. Finally, the paper discusses some implications and perspectives on the non-+-human in the study and practice of culture by particularly outlining an ethos of engaged releasement ( Gelassenheit ). This orientation will be present-ed as a letting be-come in relation to things and thinking for mediating a living sus-tainable bodiment of human and more-than-human dimensions.
Keywords: embodiment; in-between; non-human; Merleau-Ponty; practice; ddc:300